Lick Observatory Supernova Search follow-up program: photometry data release of 93 Type Ia supernovae. Issue 3 (3rd October 2019) - Stahl, Benjamin E; Zheng, WeiKang; de Jaeger, Thomas; Filippenko, Alexei V; Bigley, Andrew; Blanchard, Kyle; Blanchard, Peter K; Brink, Thomas G; Cargill, Samantha K; Casper, Chadwick; Channa, Sanyum; Choi, Byung Yun; et al.
ABSTRACT: We present BVRI and unfiltered light curves of 93 Type Ia supernovae (SNe Ia) from the Lick Observatory Supernova Search (LOSS) follow-up program conducted between 2005 and 2018. Our sample consists of 78 spectroscopically normal SNe Ia, with the remainder divided between distinct subclasses (3 SN 1991bg-like, 3 SN 1991T-like, 4 SNe Iax, 2 peculiar, and 3 super-Chandrasekhar events), and has a median redshift of 0.0192. The SNe in our sample have a median coverage of 16 photometric epochs at a cadence of 5.4 d, and the median first observed epoch is ∼4.6 d before maximum B -band light. We describe how the SNe in our sample are discovered, observed, and processed, and we compare the results from our newly developed automated photometry pipeline to those from the previous processing pipeline used by LOSS. After investigating potential biases, we derive a final systematic uncertainty of 0.03 mag in BVRI for our data set. We perform an analysis of our light curves with particular focus on using template fitting to measure the parameters that are useful in standardizing SNe Ia as distance indicators. All of the data are available to the community, and we encourage future studies to incorporate our light curves in their analyses.